Developmental mutant mouse models for external genitalia formation. (16th December 2018) - Hashimoto, Daiki; Hyuga, Taiju; Acebedo, Alvin R.; Alcantara, Mellissa C.; Suzuki, Kentaro; Yamada, Gen
Abstract : Development of external genitalia and perineum is the subject of developmental biology as well as toxicology and teratology researches. Cloaca forms in the lower (caudal) end of endoderm. Such endodermal epithelia and surrounding mesenchyme interact with various signals to form the external genitalia. External genitalia (the anlage termed as genital tubercle: GT) formation shows prominent sexually dimorphic morphogenesis in late embryonic stages, which is an unexplored developmental research field because of many reasons. External genitalia develop adjacent to the cloaca which develops urethra and corporal bodies. Developmental regulators including growth factor signals are necessary for epithelia‐mesenchyme interaction (EMI) in posterior embryos including the cloaca and urethra in the genitalia. In the case of male type urethra, formation of tubular urethra proceeds from the lower (ventral) side of external genitalia as a masculinization process in contrast to the case of female urethra. Mechanisms for its development are not elucidated yet due to the lack of suitable mutant mouse models. Because of the recent progresses of Cre (recombinase)‐mediated conditional target gene modification analyses, many developmental regulatory genes become increasingly analyzed. Conditional gene knockout mouse approaches and tissue lineage approaches are expected to offer vital information for such sexually dimorphic developmental processes. This review aims to offer recent updates on the progresses of these emerging developmental processes for the research field of congenital anomalies.